2021
DOI: 10.1002/ccd.29685
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after permanent polymer or polymer‐free stent implantation in patients with diabetes mellitus: The ReCre8 diabetes substudy

Abstract: Objectives: The purpose of this analysis was to compare target-lesion failure (TLF) of a permanent polymer zotarolimus-eluting stent (PP-ZES) versus a polymer-free amphilimus-eluting stent (PF-AES) in diabetics. Background:The improvement of outcomes with new-generation drug-eluting stent as seen in the general population is less pronounced among diabetics. The PF-AES introduces an elution-technology with potential enhanced performance in diabetics. Methods:In this subanalysis of the ReCre8 trial, patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Finally, only 4 studies [ 13 16 ] were selected for this analysis. The flow diagram for the study selection has been represented by Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, only 4 studies [ 13 16 ] were selected for this analysis. The flow diagram for the study selection has been represented by Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that our current study only involved participants with DM in contrast to the other study which included participants from the general population with coronary artery disease. A substudy of the ReCre8 trial consisting only of patients with DM showed composite of net adverse clinical events to be significantly higher with durable polymer ZES, and TLF was also higher with ZES among patients with insulin-treated DM [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Event rates among diabetic patients in this trial were higher compared to event rates in the ReCre8 trial, however rates are comparable when taking the ~4% of TLF in both stent arms in the first days into account. Interestingly, no significant difference in TLF between the stent arms was found among IDDM patients, a subgroup that showed a pronounced benefit of PF‐AES implantation after 1 year in the ReCre8 trial 4 …”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, no significant difference in TLF between the stent arms was found among IDDM patients, a subgroup that showed a pronounced benefit of PF-AES implantation after 1 year in the ReCre8 trial. 4 A prospective trial including patients undergoing PCI with implantation of second-generation DES 11 reported comparable event rates for TLF-components among their diabetic population. Cardiac death occurred in 5% after 3 years (ReCre8 5.0%) and target-lesion revascularization in 5.5% (ReCre8 5.6%).…”
Section: T a B L E 1 Clinical Events 3 Years After Stent Implantation...mentioning
confidence: 99%
See 1 more Smart Citation